2013
DOI: 10.1186/2040-2392-4-1
|View full text |Cite
|
Sign up to set email alerts
|

Task-related functional connectivity in autism spectrum conditions: an EEG study using wavelet transform coherence

Abstract: BackgroundAutism Spectrum Conditions (ASC) are a set of pervasive neurodevelopmental conditions characterized by a wide range of lifelong signs and symptoms. Recent explanatory models of autism propose abnormal neural connectivity and are supported by studies showing decreased interhemispheric coherence in individuals with ASC. The first aim of this study was to test the hypothesis of reduced interhemispheric coherence in ASC, and secondly to investigate specific effects of task performance on interhemispheric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
85
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(91 citation statements)
references
References 78 publications
(129 reference statements)
5
85
0
1
Order By: Relevance
“…As glutamate does not easily pass the blood-brain barrier, it is somewhat unclear whether the elevated plasma glutamate levels reflect CNS levels of the amino acid. Direct measurement from post-mortem brain tissue using high performance liquid chromatography has shown elevations in glutamate and glutamine from the anterior cingulate cortex in 7 individuals with autism (Shimmura et al 2013). Attempts to measure in vivo brain glutamate levels non-invasively using magnetic resonance spectroscopy have resulted in slightly more variable findings, however, as discussed below.…”
Section: Elevated Blood Plasma and Serum In Autismmentioning
confidence: 99%
See 1 more Smart Citation
“…As glutamate does not easily pass the blood-brain barrier, it is somewhat unclear whether the elevated plasma glutamate levels reflect CNS levels of the amino acid. Direct measurement from post-mortem brain tissue using high performance liquid chromatography has shown elevations in glutamate and glutamine from the anterior cingulate cortex in 7 individuals with autism (Shimmura et al 2013). Attempts to measure in vivo brain glutamate levels non-invasively using magnetic resonance spectroscopy have resulted in slightly more variable findings, however, as discussed below.…”
Section: Elevated Blood Plasma and Serum In Autismmentioning
confidence: 99%
“…Shimmura et al (2011) reported that while plasma levels of glutamate were significantly higher in children with autism, glutamine levels were significantly reduced compared to controls. A recent study by the same group of the anterior cingulate cortex in post-mortem tissue samples found that kidney-type glutaminase levels were reduced in the autism group, but not levels of liver-type glutaminase, glutamate synthetase or the glutamate dehydrogenases (Shimmura et al 2013). This was interpreted to mean that the glutamate-glutamine cycle might be shifted in the direction of glutamine, but on the surface this would seem to be at odds with most of the plasma glutamate and 1H-MRS results for glutamate proper, which suggest elevated levels in autism.…”
Section: Evidence Of Altered Glutamate Metabolism In Autismmentioning
confidence: 99%
“…Studies of functional connectivity have identified a general pattern of long-range under-connectivity and short-range over-connectivity in ASD, with results varying based on regions and frequency bands of interest [40][41][42]. Functional connectivity and coherence during cognitive and perceptual tasks have also yielded some promising findings in distinguishing ASD from typical development, with differences in connectivity patterns, particularly in interhemispheric coherence, during tasks such as face and object processing, picture naming, set-shifting [43][44][45][46]. A recent study by Eldridge et al (2014) examined signal complexity through MSE in EEG recordings from an auditory oddball event-related potential (ERP) paradigm in young children ages 6-10 years old and found that MSE is a useful feature for classification of children as ASD or typically developing [47 & ].…”
Section: Diagnostic Biomarkers In Autism Spectrum Disordermentioning
confidence: 99%
“…As in the imaging reports, the resulting evidence is conflicting and inconsistent. Twenty-one studies in the last decade have been published; 11 evaluated resting state (Murias et al 2007;Coben et al 2008;Barttfeld et al 2011;Bosl et al 2011;Duffy and Als 2012;Mathewson et al 2012;Sheikhani et al 2012;Leveille and Hannagan 2013;Peters et al 2013;Machado et al 2015), eight were task related (Isler et al 2010;Lazarev et al 2010;Catarino et al 2013;Garcia Dominguez et al 2013;Carson et al 2014;Orekhova et al 2014;Righi et al 2014;Lazarev et al 2015;Machado et al 2015); one obtained during non-rapid eye movement (NREM) sleep (Lazar et al 2010) and one obtained during rapid eye movement (REM) sleep (Leveille et al 2010). It is not possible to directly compare these studies as the acquisition paradigm, the age of the subjects, Figure 3.…”
Section: Aberrant Connectivity In Autismmentioning
confidence: 99%